1 H NMR-based metabolomics exploring urinary biomarkers correlated with proteinuria in focal segmental glomerulosclerosis a pilot study - Kalantari, Shiva (Magnetic resonance in chemistry : MRC, 2016)
Copyright © 2016 John Wiley & Sons, Ltd.